Effect of Saffron on serum zinc and copper in patients with metabolic syndrome - Maryam Saberi-Karimian; Susan Darroudi; Fatemeh Shaghi; Shima Tavallaei; Hamide Safarian; Gordon A. Ferns; Majid Ghayour-Mobarhan; Tayyebeh Kermany; Maryam Shemshian (Lorestan University of Medical Sciences, 2021)
Introduction: The prevalence of metabolic syndrome (MetS) is increasing globally. Previous studies have shown that saffron has anti-oxidative effects. Copper (Cu) and zinc (Zn) are important trace elements involved in antioxidant protection. We aimed to investigate the effects of saffron supplements on serum levels of Cu, Zn and SOD in subjects with MetS. Methods: This randomized double-blind clinical trial comprised 70 subjects with MetS, aged18-75 years, who referred to the Nutrition Clinic in Ghaem Hospital. They were divided into 2 groups: 1- saffron group: taking a capsule of saffron 100 mg/kg/day (50 mg twice a day) (n=35); 2- placebo group: taking a capsule of placebo (twice a day) (n=35), for a period of 12 weeks. Atomic absorption spectrophotometry was used to measure serum zinc and copper levels in all subjects. Serum SOD activity determined using pyrogallol indirect spectrophotometric assay. SPSS version 18 was used for all the statistical analysis. Results: Fifty-six subjects completed the study. There were no significant differences in baseline features between the saffron and placebo groups (p> 0.05). The changes in serum zinc levels at baseline and after 12 weeks of intervention were significant between the saffron and placebo groups (p=0.041), (Table 2). While, there were no significant differences changes in serum copper, ZN/Cu and SOD1 between 2 study groups before and after the intervention. Conclusion: The results of current study showed that saffron supplementation for a period of 12 weeks can increase serum Zn level in patients with MetS.